Identification of Key Gene Networks Controlling Soluble Sugar and Organic Acid Metabolism During Oriental Melon Fruit Development by Integrated Analysis of Metabolic and Transcriptomic Analyses - Cheng, Hong; Kong, Weiping; Tang, Taoxia; Ren, Kaili; Zhang, Kaili; Wei, Huxia; Lin, Tao (Frontiers in Plant Science, 2022)
Oriental melon (Cucumis melo var. acidulus) is one of the most economically important fruit crops worldwide. To elucidate the molecular basis related to soluble sugar and organic acid metabolism in the fruits of two oriental melon cultivars with different sweetness, we performed integrated metabolomic and transcriptomic analyses of the fruits of ‘Tianbao’ (A) with high sweetness and ‘Xiaocuigua’ (B) with low sweetness at different ripening stages. The high accumulation of sucrose, D-glucose, D-(+)-raffinose and the relatively lower citric acid and malic acid might contribute to the sweet taste of A. By screening the differentially expressed genes (DEGs) and correlation analysis of the DEGs and differentially accumulated metabolites, we deduced that the B cultivar might promote the conversion of glucose and fructose into intermediate compounds for downstream processes such as glycolysis. The tricarboxylic acid cycle might also be enhanced compared to A, thus resulting in the differential accumulation of soluble sugars and organic acids, ultimately causing the taste difference between the two oriental melon cultivars. Our finding provides important information for further exploring the metabolic mechanisms of soluble sugars and organic acids in oriental melon.